COMUNIDADES FAXINALENSES NO MUNICÍPIO DE RIO AZUL-PR: gênese, características e transformações nos padrões espaciais de povoamento - Soares, Joélcio Gonçalves (2012)
This dissertation is based on the assumption that communities are localities where social processes and relations are lived in space and time. In this context, the municipality of Rio Azul has been chosen to understand the formation and dynamics of rural environments through their communities. The municipality is located in Central-South Paraná and a large portion of its rural communities can be identified as faxinais. Faxinais are traditional communities of a land use pattern that clearly divides “terras de criar” (pasture land), under common use, from “terras de plantar” (cultivation land), which is planted by individual families. The research is mainly targeted at spatial settlement patterns and temporal-spatial differentiations of faxinal communities. In this context, the genesis of those rural communities, which have been structured as faxinais, has been investigated including an analysis of the socio-spatial transformations that have been occurred between 1960 and today. For this purpose, the research has followed different steps. First, a bibliographical research concerning theoretical and conceptional reflections has been made; this step alos has involved statistical and historical data of the municipality and its rural communities. Second, interpretations of the Topographical Map Rebouças (BRASIL 1973) and Google Earth Images (2011) have been used to understand the temporal-spatial transformations of the areas of these rural communities. In a third step, fieldwork has been conducted on the base of observation and interview techniques. Our investigation has paved a new analytical approach to faxinal communities, parting from the perspective of its spatial configurations. 4 types of dynamic settlement structures have been identified in the case of the Rio Azul municipality: a) Faxinais with a nuclear settlement structure; b) Faxinais with a linear settlement structure, c) Faxinais with a poly-nuclear settlement structure; d) Faxinais with a mixed settlement structure.